Evaluation of the Computed Tomography Number for Water, Field Uniformity, Image Noise and Contrast Resolutions in Kano Metropolis, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Quality control (QC) tests for computed tomography (CT) scanners are primarily concerned with the maintenance of CT scanner at the optimum operational conditions for providing the required diagnostic information at the least possible exposure to ionising radiation.Aims:The study was aimed at evaluating a CT number for water, field uniformity, image noise and contrast resolutions in Kano metropolis using phantom and assuring optimum operational condition of the equipment.Materials and Methods:A prospective, crosssectional design was employed. Four scanners tagged CT scanner I–IV were included in the study. CT number for water, field uniformity, noise, as well as highcontrast resolution (HCR) and lowcontrast resolution were tested using head CT water phantom.Results:CT scanner I, III and IV have passed a CT number for water and field uniformity tests (0.3, −0.48 and − 1.36), but scanner II failed the test (−4.38). However, the entire scanners failed noise (4.5, 8.75, 4.90 and 4.93); while only scanner III passed the HCR QC test (bars were countable at the 3rd bar pattern), scanners I, II and IV failed HCR test (bars were countable at 5th, 6th and 4th bar patterns). All the studied scanners failed lowcontrast resolution test (margins appear sharp at the 4th hole) in scanners I, II and IV and the hole was not demonstrated in the phantom image of scanner III.Conclusion:Majority of the CT scanners in Kano metropolis passed the tests for the CT number for water and field uniformity but revealed some inadequate levels of noise, HCR and lowcontrast resolution tests.